Sowing methods for pasture establishment in semi-arid regions - SWAMINATHAN, C; KANNAN, K (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during 1997-99 to find out the best sowing method for establishing pastures at Pudukkottai, Tamil Nadu. Three pasture grasses, viz. Andropogon gayanus Kunh, Cenchrus setigerus Vahl and Pennisetum polystachion (L.) Schuttes were tested against four sowing methods for their performance and productivity. The results revealed that direct seeding is the best method of sowing for Cenchrus setigerus and Pennisetum polystachion with higher green fodder production of 5.61 and 22.3 tonnes/ha/year respectively, while broadcasting seeds in sand mixture is ideal for Andropogon gayams (2.5 tonnes/ha/year).